2014
DOI: 10.1007/s13277-014-2480-1
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of TRPM8 is associated with poor prognosis in urothelial carcinoma of bladder

Abstract: Transient receptor protein (TRP) channels are frequently associated with tumors and are correlated to patient's outcome. We firstly investigated TRP channel melastatin 8 (TRPM8) expression in urothelial carcinoma of bladder (UCB) and its correlation with UCB clinicopathological features and additionally evaluated the association between TRPM8 expression and patients' survival rate to elucidate its role in bladder oncogenesis. Real-time quantitative reverse transcription polymerase chain reaction (qRT-PCR) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 22 publications
2
19
0
1
Order By: Relevance
“…Besides prostate carcinoma, the expression levels of TRPM8 were significantly higher in urothelial carcinoma of bladder tissues than in non-cancerous urothelial tissues [ 60 ]. A positive association between the expression levels of TRPM8 and histological grade or tumor stage was established.…”
Section: Trpm8 Channels In Cancersmentioning
confidence: 99%
“…Besides prostate carcinoma, the expression levels of TRPM8 were significantly higher in urothelial carcinoma of bladder tissues than in non-cancerous urothelial tissues [ 60 ]. A positive association between the expression levels of TRPM8 and histological grade or tumor stage was established.…”
Section: Trpm8 Channels In Cancersmentioning
confidence: 99%
“…Previous studies have reported on the associations between certain cancer types and TRPM ion channels (7,(15)(16)(17)(18)(19)(20)(21); however, to the best of our knowledge, there have been no studies in the literature that have investigated the role of these ion channels in bladder cancer. In this original study, we aimed to determine whether bladder cancer is associated with the mRNA expression levels of TRPM ion channel genes, and whether this could merit further study with the aim of establishing novel treatment modalities.…”
Section: Introductionmentioning
confidence: 99%
“…The expression levels of TRPM8 mRNA in bladder tissue from urothelial carcinoma subjects were also significantly higher than those in matched noncancerous tissues (P = 0.016) (Xiao et al, 2014). Expression of the TRPM8 protein in bladder tissue from urothelial carcinoma subjects was significantly and positively associated with histological grade (P = 0.039) and tumor stage (P = 0.037) (Xiao et al, 2014). Significant correlation has been found between high TRPM8 expression and poor cumulative survival in patients with urothelial carcinoma of the bladder, suggesting that overexpression of TRPM8 may play a role in the pathogenesis and progression of the disease (Xiao et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, TRPM8 has higher expression in prostate cancer tissue than in normal prostate tissue, and has also been detected in tumors of the breast, colon, lung, skin, and pancreas (Tsavaler et al, 2001;Yee et al, 2010;Okamoto et al, 2012). The expression levels of TRPM8 mRNA in bladder tissue from urothelial carcinoma subjects were also significantly higher than those in matched noncancerous tissues (P = 0.016) (Xiao et al, 2014). Expression of the TRPM8 protein in bladder tissue from urothelial carcinoma subjects was significantly and positively associated with histological grade (P = 0.039) and tumor stage (P = 0.037) (Xiao et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation